The WHO Global Tuberculosis 2021 Report – not so good news and turning the tide back to End TB - Chakaya, Jeremiah; Petersen, Eskild; Nantanda, Rebecca; Mungai, Brenda N.; Migliori, Giovanni Battista; Amanullah, Farhana; Lungu, Patrick; Ntoumi, Francine; Kumarasamy, Nagalingeswaran; Maeurer, Markus; Zumla, Alimuddin (International journal of infectious diseases, 2022)
•Tuberculosis remains a major global public health threat.•The End TB Strategy and United Nations targets for TB are all off track.•The COVID-19 pandemic aggravated an already sub-optimal global TB response.•Achieving TB targets will require optimized use of existing tools and new tools.•Social determinants and financing of TB need to be addressed. To review the data presented in the 2021 WHO global TB report and discuss the current constraints in the global response. The WHO global TB reports, consolidate TB data from countries and provide up to date assessment of the global TB epidemic. We reviewed the data presented in the 2021 report. We noted that the 2021 WHO global TB report presents a rather grim picture on the trajectory of the global epidemic of TB including a stagnation in the annual decline in TB incidence, a decline in TB notifications and an increase in estimated TB deaths. All the targets set at the 2018 United Nations High Level Meeting on TB were off track. The sub-optimal global performance on achieving TB control targets in 2020 is attributed to the on-going COVID-19 pandemic, however, TB programs were already off track well before the onset of the pandemic, suggesting that the pandemic amplified an already fragile global TB response. We emphasize that ending the global TB epidemic will require bold leadership, optimization of existing interventions, widespread coverage, addressing social determinants of TB and importantly mobilization of adequate funding required for TB care and prevention.